Revisão taxonômica das espécies de Hemigrammus Gill, 1858 (Characiformes: Characidae) da bacia do rio Paraguai. - Ota, Rafaela Priscila (2010)
A revision of the species within Hemigrammus from rio Paraguai basin was conducted, involving the analysis of about 1330 specimens of Hemigrammus. Five species were redescribed: H. lunatus, H. mahnerti, H. neptunus, H. tridens and H. ulreyi, and three undescribed species were identified (Hemigrammus sp. 1, Hemigrammus sp. 2, and Hemigrammus sp. 3). Hyphessobrycon maxillaris was considered a junior synonym of Hemigrammus lunatus. Significant range extensions are provided for Hemigrammus ulreyi (now recorded for the rio Paraguai and rio Paraná basins in Paraguay), H. mahnerti and H. neptunus (both now recorded for the rio Madeira and rio Paraguai basins in Brazil), as well as the confirmation of occurrence of H. tridens throughout the entire rio Paraguai basin. Records of the occurrence of H. ocellifer and H. marginatus at rio Paraguai basin are herein considered to be based on misidentifications of, respectively, H. neptunus and Hemigrammus sp. 1. Hooks on pelvic and anal fins in mature males are herein detected for H. lunatus, H. tridens and H. ulreyi, and reported for the first time for the last two species. Three Hemigrammus species occurring in the rio Paraguai basin are identified as miniatures: H. mahnerti, H. tridens and Hemigrammus sp. 1. The similarity between fish fauna from rio Paraguai basin, middle rio Paraná and rio Guaporé basins was highlighted. Likewise, the putative phylogenetic relationship of the species within Hemigrammus and with the remaining genera of Characidae currently considered as Incertae Sedis, as well as the importance of taxonomic revisions, including information about patterns of distribution, ecology, size, sexual dimorphism and morphological details of the external structures are discussed.